2010
DOI: 10.1159/000320347
|View full text |Cite
|
Sign up to set email alerts
|

Resource Utilization in Patients with Brain Metastases Managed with Best Supportive Care, Radiotherapy and/or Surgical Resection: A Markov Analysis

Abstract: Objective: In spite of the large number of patients and increasing financial pressure on health care budgets worldwide, limited data on resource utilization after diagnosis of brain metastases are available. Methods: Prospective data were collected on all patients diagnosed with brain metastases during a time period of 2 years (n = 53). Treatment was best supportive care (BSC), primary radiotherapy (RT) and/or surgical resection. Eighty-five percent of patients had active extracranial disease. Costs were calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 23 publications
(16 reference statements)
0
18
0
Order By: Relevance
“…Several authors reported median survival of 1.3 months to 2.1 months in patients managed with best supportive care without radiotherapy. 3,15,23 The current survival data in RPA class III and the most unfavorable GPA class (0-1 point; Table 3) are in the same range. Therefore, prospective comparison of best supportive care versus cranial radiotherapy in patients with limited prognosis is justified.…”
Section: Argument References Commentmentioning
confidence: 68%
See 1 more Smart Citation
“…Several authors reported median survival of 1.3 months to 2.1 months in patients managed with best supportive care without radiotherapy. 3,15,23 The current survival data in RPA class III and the most unfavorable GPA class (0-1 point; Table 3) are in the same range. Therefore, prospective comparison of best supportive care versus cranial radiotherapy in patients with limited prognosis is justified.…”
Section: Argument References Commentmentioning
confidence: 68%
“…Of course, increases in SRS and chemotherapy utilization as well as introduction of new classes of drugs will lead to increased cost. In our recent analysis, we found this cost to be €43,955 per life year for the average patient with brain metastases, 3 and this does not exceed treatment costs in comparable oncologic scenarios. It is also noteworthy that better individualization of treatment in some cases might save resources as emphasized by the increasing use of short-course WBRT.…”
Section: Argument References Commentmentioning
confidence: 86%
“…Brain metastases are known to severely impact a patient's quality-of-life (physical, cognitive, and functional impairments) 24,31,33 , as well as to result in high healthcare resource utilization 37 and substantial clinical 43 , economic 27 , and caregiver 32 burden. In this study, we found that the development of brain metastases is associated with a substantial treatment burden, resource use, and costs in ALKþ NSCLC patients (identified by the use of crizotinib).…”
Section: Discussionmentioning
confidence: 99%
“…A probable explanation for the differences in cost distribution is that using targeted agents for the treatment of (brain) metastatic ALKþ NSCLC increases pharmacy costs, but reduces the use of inpatient services, possibly indicating that the disease has been managed (for a period of time). Another study evaluating the costs of treating brain-metastatic cancer patients (of which 55% were lung cancer patients) also found that brain metastases are associated with a significant economic burden, concluding that the total costs per year of life amounted to $62,130 (where less than 25% of the patients survived the first year of treatment) 37 . This study has demonstrated that the development of brain metastases, common in ALKþ NSCLC, can be costly and can present a substantial clinical burden.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation